1995
DOI: 10.1002/gcc.2870120110
|View full text |Cite
|
Sign up to set email alerts
|

Inversion‐associated translocations in acute myelomonocytic leukemia with eosinophilia

Abstract: Cytogenetic studies of three acute myelomonocytic leukemias with bone marrow eosinophilia (M4EO) revealed chromosome 16 inversion associated with additional abnormalities. The inverted chromosome 16 was involved in two patients. Fluorescence in situ hybridization (FISH) experiments with a YAC probe detecting inv(16) showed that the translocation breakpoints involving chromosome 16 did not implicate the inversion breakpoints. FISH can thus distinguish between true variant translocations and translocations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Inv(16)/t(16; 16), can be underestimated for technical reasons, such as poor chromosome morphology or analysis of cells belonging to a residual normal clone. Masked inv(16) due to inverted chromosomes being involved in translocations with other chromosomes or to submicroscopic rearrangements, has been detected in leukemias with normal karyotype or trisomy of chromosomes 8 and/or 22 (27, 28). Trisomy 8, 21, and 22 are additional karyotypic abnormalities in about half the patients with inv(16)/t(16; 16).…”
Section: Typical Chromosomal Changes Generating Fusion Transcriptsmentioning
confidence: 99%
“…Inv(16)/t(16; 16), can be underestimated for technical reasons, such as poor chromosome morphology or analysis of cells belonging to a residual normal clone. Masked inv(16) due to inverted chromosomes being involved in translocations with other chromosomes or to submicroscopic rearrangements, has been detected in leukemias with normal karyotype or trisomy of chromosomes 8 and/or 22 (27, 28). Trisomy 8, 21, and 22 are additional karyotypic abnormalities in about half the patients with inv(16)/t(16; 16).…”
Section: Typical Chromosomal Changes Generating Fusion Transcriptsmentioning
confidence: 99%
“…A number of cases of inv( 16) associated with chromosomal translocations have been described for the M4eo subtype of AML (reviewed in Berger et al, 1995). T h e phenomenon is poorly understood and may indeed be limited to inv(l6).…”
Section: B: T(l;))inv())(q212q263) With Der(l) and Der(3)mentioning
confidence: 99%
“…In such cases, however, band 16q22 rather than 16p13 was mostly involved. Berger et al (1995), in performing FISH with the YAC 854E2, showed that what appeared as variant translocations of 16q22 in two cases of AML-M4Eo contained a masked inv(16). In both cases, an inversion involving MYH11 and CBFB plus a translocation occurred in the same chromosome 16 as two independent events, with different breakpoints.…”
Section: Discussionmentioning
confidence: 99%